2011
DOI: 10.1016/j.jvs.2011.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic kidney disease on carotid plaque vulnerability

Abstract: In patients with CKD and advanced carotid artery stenosis, morphologic changes in plaque composition may contribute to plaque vulnerability and consequently to the risk of cerebrovascular events. Furthermore, relevant serum markers of inflammation, vascular calcification, and vessel wall degradation might be an indication of stroke risk in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 38 publications
0
23
0
2
Order By: Relevance
“…Although Davaine et al 34 showed that vascular calcification is associated with plaque stability, other studies revealed ambiguous results. 26,33,35 Howard et al 33 did not find any relationships between calcification, intraplaque hemorrhage, or lymphocyte infiltration and stroke occurrence. In accordance with the latter findings, our study confirmed the assumption that increased calcification or higher amounts of inflammatory infiltration were also not associated with a history of neurological symptoms.…”
mentioning
confidence: 95%
“…Although Davaine et al 34 showed that vascular calcification is associated with plaque stability, other studies revealed ambiguous results. 26,33,35 Howard et al 33 did not find any relationships between calcification, intraplaque hemorrhage, or lymphocyte infiltration and stroke occurrence. In accordance with the latter findings, our study confirmed the assumption that increased calcification or higher amounts of inflammatory infiltration were also not associated with a history of neurological symptoms.…”
mentioning
confidence: 95%
“…Furthermore serum matrix metalloproteinases were found raised in cases of moderate to severe renal dysfunction patients and these result in progression of plaque and degradation of overlying fibrous cap. 23 Experimental data support the view that renal dysfunction increases foam cell generation by stimulating macrophage entry into vascular endothelium. 24 Further studies have revealed an accelerated infarct expansion, active inflammation and oxidative stress in patients having ACS with renal dysfunction.…”
Section: Discussionmentioning
confidence: 75%
“…CKD patients display advanced carotid atherosclerosis with more frequently unstable or ruptured plaques due to composition changes (less collagen, more calcified) and this explains the 3-fold higher prevalence of remote cerebrovascular events in these patients compared to non-CKD [21]. …”
Section: Ischaemic Strokementioning
confidence: 99%